INTERNALISASI NILAI NILAI ANTIKORUPSI DALAM KURIKULUM PENDIDIKAN - Zainudin Hasan; M. Reyhan Al Rizkie Sumbahan; Agam Izazi; M. Rakha Wira Yudha (JURNAL ILMIAH PENELITIAN MAHASISWA, 2026)
Corruption is a serious problem that has become deeply rooted in Indonesia’s social, economic, and political systems, causing significant financial losses to the state and contributing to moral degradation in society. Efforts to eradicate corruption cannot rely solely on repressive legal approaches but must also involve sustainable preventive measures through the education sector. Education plays a strategic role in instilling anti-corruption values from an early age to shape a generation with strong character and integrity. This study aims to examine the internalization of anti-corruption values within the educational curriculum as an effort to prevent corruption. The method used is a literature review by analyzing various relevant books and scientific journals. The results show that the integration of anti- corruption values into the curriculum can foster honesty, responsibility, discipline, and integrity among students. However, its implementation still faces several challenges, such as limited teacher understanding, inadequate facilities, and insufficient policy and school culture support. Therefore, systematic, structured, and collaborative strategies among the government, educational institutions, and society are required to optimize the internalization of anti-corruption values in education, thereby creating a generation with integrity that actively contributes to corruption prevention in the future.